Effects of NaCl stress on seed germination attributes of periwinkle (Catharanthus roseus L.) and corn poppy (Papaver rhoeas L.) plants - Saeb, H.; Khayyat, M.; Zarezadeh, A.; Moradinezhad, F.; Samadzadeh, A.; Safaee, M. (Plant Breeding and Seed Science, 2012)
The present research was conducted to evaluate the effects of salinized water with NaCl on seed germina- tion of Periwinkle and Corn Poppy. Treatments were: A) H2O- distilled water (control); B) sodium chloride solutions (5, 10, 20, 40 and 80 mM). Application of the highest NaCl concentration (80mM) significantly reduced germination percentage and mean germination time of both species, although increased the day of 50% germination. Increment of salinity concentration was led to the reduction of radicle length in Periwinkle. The seedling fresh weight and water content and radicle length of Corn Poppy were decreased in both levels of 20 and 80 mM, and seedling dry weight was unaffected by treatments. It is concluded that both species are tolerant to NaCl salinity up to 80 mM during germination stage.